1994
DOI: 10.1007/bf00327956
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Aeromonas hydrophila and Listeria monocytogenes on fresh vegetables stored under moderate vacuum

Abstract: Storage at 6.5°C under moderate vacuum effectively prevented growth of Aeromonas hydrophila on chicory endive, but had only a limited inhibitory effect on the growth of the organism on mung bean sprouts. Growth of Listeria monocytogenes on chicory endive was strongly stimulated under these conditions, whereas it was decreased on mung-bean sprouts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…This suggests that the presence of endogeneous microflora on trout can inhibit the growth of Listeria sp. Similar results have been observed in studies of minimally processed vegetable samples showing an inhibitory effect of endogeneous microflora on L. monocytogenes (Bennik et al, 1996;Aytaç and Gorris, 1994;Carlin and Nguyen-the, 1994). Randell et al (1997) found that the sensory quality of packed trout fillets gradually becomes unfit during an 11-day storage at 2°C regardless of the gas-packaging methods.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that the presence of endogeneous microflora on trout can inhibit the growth of Listeria sp. Similar results have been observed in studies of minimally processed vegetable samples showing an inhibitory effect of endogeneous microflora on L. monocytogenes (Bennik et al, 1996;Aytaç and Gorris, 1994;Carlin and Nguyen-the, 1994). Randell et al (1997) found that the sensory quality of packed trout fillets gradually becomes unfit during an 11-day storage at 2°C regardless of the gas-packaging methods.…”
Section: Discussionsupporting
confidence: 80%
“…It is likely that both nisin and LG have the potential to reduce some spoilage bacteria individually; however, in a mixed population on a dynamic food product, their effect may be inconclusive. However, it may be that endogenous bacteria could inhibit the growth of L. monocytogenes in smoked trout (Shin et al, ) and vegetables (Aytac & Gorris, ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation of growth retardation of L. monocytogenes in salmon roe could be the presence of endogenous microflora. The inhibitory effects of competitive microflora against L. monocytogenes were observed in studies involving minimally processed vegetable samples (Aytaç and Gorris 1994; Carlin and Nguyen‐the 1994; Bennik and others 1996) and seafood samples (Brillet and others 2005). Lactic acid bacteria are known to inhibit L. monocytogenes (Pucci and others 1988; Schillinger and Lucke 1989; Nilsson and others 1999; Amézquita and Brashears 2002).…”
Section: Discussionmentioning
confidence: 99%